PENGARUH SUASANA CAFE, GAYA HIDUP, DAN KERAGAMAN PRODUK TERHADAP MINAT BERKUNJUNG KEMBALI DI JHONNIA CAFE - Efdison, Zefri; Izzety, Julifa; Yadewani, Dorris; Harahap, Erni Febrina (Gapenas Publisher, 2025)
This research is to determine the influence of café atmosphere, lifestyle, and product diversity on the interest of visiting Jhonnia Cafe again. This research was conducted to test whether there is an influence between variables, namely specifically hypothesis tests will be carried out in structural equations. The data analysis technique used in this study is the Multiple Liner Regression analysis technique. The results of this study show that the atmosphere of the café has a significant effect on the Interest in Returning (Y). This has been proven from the results of the t-test (Partial), which states that the calculated t-value is obtained as much as 0.069 > the t-value of the table 1.98498 with a significant level of 0.505 > 0.05. Lifestyle has a significant effect on Interest in Returning (Y). This has been proven from the results of the t-test (Partial), which states that the calculated t-value is obtained as 0.768< the t-value of the table is 1.98498 with a significant level of 0.444 > 0.05. Product Diversity has a significant effect on Interest in Returning Visits, This has been proven from the results of the t-test (Partial), which states that the calculated t-value is obtained as 1,509< the t-value of the table is 1.98498 with a significant level of 0.135 >0.05. The results of the study showed that the variables of Cafe Atmosphere, Lifestyle, and Product Diversity simultaneously had a significant effect on the Interest in Returning Visitors. This has been proven from the results of the F (Simultaneous) test, which states that the f value calculated > f table is (1.747 > 2.47) and with a significance value = .0163b >0.05.